2018
DOI: 10.1039/c7fd00217c
|View full text |Cite
|
Sign up to set email alerts
|

Stability and mobility of supported Nin (n = 1–10) clusters on ZrO2(111) and YSZ(111) surfaces: a density functional theory study

Abstract: The performance of supported metal catalysts, such as nickel nanoparticles decorating yttria-stabilized zirconia (YSZ), depends on their microstructure and the metal-support interface. Here, we have used spin polarized density functional theory (DFT) to evaluate different Ni cluster geometries and determined the electronic structure of the most stable configurations. We have described the interaction of Nin (n = 1-10) clusters supported on the cubic ZrO2(111) and YSZ(111) surfaces, which show a preference for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
1
5
0
1
Order By: Relevance
“…Moreover, it was observed that one of these cations will be located at the (111) surface and the oxygen vacancy at the subsurface. Similar results were later obtained by Cadi-Essadek et al [ 28 , 30 , 47 ] and Ricca et al [ 48 ] using DFT approaches (generalized gradient approximation (GGA) and hybrid functionals). It is worth noticing that alternative configurations have also been identified by Chaopradith et al [ 49 ], which may be appropriate for higher dopant concentrations.…”
Section: Resultssupporting
confidence: 84%
“…Moreover, it was observed that one of these cations will be located at the (111) surface and the oxygen vacancy at the subsurface. Similar results were later obtained by Cadi-Essadek et al [ 28 , 30 , 47 ] and Ricca et al [ 48 ] using DFT approaches (generalized gradient approximation (GGA) and hybrid functionals). It is worth noticing that alternative configurations have also been identified by Chaopradith et al [ 49 ], which may be appropriate for higher dopant concentrations.…”
Section: Resultssupporting
confidence: 84%
“…Density functional theory (DFT) [28,29,31,42,43] Molecular dynamics (MD) [32,[37][38][39] Kinetic Monte Carlo The above five scales and the corresponding modelling approaches are reviewed in the following sections. Microscale models are employed to study the detailed electronic structure of materials as well as the atomic/molecular interactions.…”
Section: Microsca Lementioning
confidence: 99%
“…Cadi-Essadek et al [29] conducted DFT modelling to assess the stability of various Ni cluster configurations on the ZrO2 and YSZ using clustering energy as an index. Besides, the cohesive energy and the interaction energy was calculated to understand the interaction among Ni atoms, and the interaction between the electrolyte surface and the DFT was also used to evaluate the catalytic/electrocatalytic reactions of gaseous reactants in porous materials [30].…”
Section: Density Functional Theory (Dft)mentioning
confidence: 99%
“…Here, we chose Ni dimer to clarify the interaction between Ni clusters and h-BNNS [48][49][50][51]. As shown in Fig.…”
Section: Dft Calculations About Electronic Properties Of the Catalystsmentioning
confidence: 99%